More Beautiful Areas: Performativity and Presence in the Integrated Soundtrack - Adam Melvin (Alphaville: Journal of Film and Screen Media, 2024)
In 2019, I presented a paper at a conference in NUI Maynooth, Ireland that used Kevin Donnelly’s notion of the soundtrack as spectre as the starting point for discussing performativity and presence in the films of Russian director Andrey Zvyagintsev. During the discussion that followed, Danijela Kulezic-Wilson, who was in attendance, raised several observations concerning the relevance of Donnelly’s concept to her own research exploring the integrated soundtrack. This paper essentially seeks to continue that conversation. By revisiting several examples explored in Kulezic-Wilson’s chapter on “Soundtrack’s Liminal Spaces” in Sound Design Is the New Score, alongside others including Nick Cave’s score for The Proposition (John Hillcoat, 2005) and Birdman (Alejandro Iñárritu, 2014), I explore to what extent Donnelly’s analogy can be expanded to consider instances in film where the foregrounding of tactile musical gestures and spatial placement within the audio mix results in a distinctly performative, quasi-physical sensibility that challenges the “insubstantial” status of Donnelly’s spectral presence. Drawing on a broad framework of theoretical concepts including Miguel Mera’s discussion of the haptic score and Paul Sanden’s network of liveness, this paper aims to provide a complimentary perspective to an important aspect of Danijela Kulezic-Wilson’s significant contribution to the study of film sound and music.